2011
DOI: 10.1093/nar/gkr101
|View full text |Cite
|
Sign up to set email alerts
|

On the structure and dynamics of the complex of the nucleosome and the linker histone

Abstract: Several different models of the linker histone (LH)–nucleosome complex have been proposed, but none of them has unambiguously revealed the position and binding sites of the LH on the nucleosome. Using Brownian dynamics-based docking together with normal mode analysis of the nucleosome to account for the flexibility of two flanking 10 bp long linker DNAs (L-DNA), we identified binding modes of the H5-LH globular domain (GH5) to the nucleosome. For a wide range of nucleosomal conformations with the L-DNA ends le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
59
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(70 citation statements)
references
References 44 publications
11
59
0
Order By: Relevance
“…S1). Among several computation-based models of the gH1/H5-nucleosome complex (30)(31)(32)46), two of them show similarities to our model in terms of both location and orientation of gH1 in the complex (30,31). In addition, our model is consistent with several other experimental observations.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…S1). Among several computation-based models of the gH1/H5-nucleosome complex (30)(31)(32)46), two of them show similarities to our model in terms of both location and orientation of gH1 in the complex (30,31). In addition, our model is consistent with several other experimental observations.…”
Section: Discussionsupporting
confidence: 86%
“…In the symmetric class, gH1/gH5 binds to the nucleosomal DNA at the dyad and interacts with both linker DNAs (16,17,27,28). In the asymmetric class, gH1/gH5 binds to the nucleosomal DNA in the vicinity of the dyad axis and to 10 bp (27,(29)(30)(31)(32) or 20 bp (19,29,33,34) of one linker DNA, or is located inside the DNA gyres, where it interacts with histone H2A (35). In addition, Zhou and colleagues also characterized the orientation of gH5 in the gH5-nucleosome complex (29).…”
Section: Structural Insights Into the Histone H1-nucleosome Complexmentioning
confidence: 99%
“…This accessory protein consists of a rigid and well-folded globular head linked to a short N-terminal and a long C-terminal domains, both of which are intrinsically disordered and essential for cell regulation [38]. Although all-atom trajectories of the nucleosome-linker histone complex are too costly, the Wade lab has combined docking, Brownian dynamics, and normal mode analysis to simulate the binding to the H5 globular domain in the nucleosome (without core histone tails) [39 • ]. Their studies suggest that H5 can adopt various docking positions near the nucleosome's dyad axis rather than a single symmetric position where it interacts with both linker DNAs as previously observed [40].…”
Section: Atomistic Simulations Of Chromatin Componentsmentioning
confidence: 99%
“…Linker histones (LH) are highly flexible and can adopt various conformations upon binding to nucleosomes [39 • ]. Studies have shown that N-terminal domain of the LH does not have significant effect on the higher-order chromatin organization; however, the intrinsically disordered C-terminal domain can be a crucial factor in chromatin architecture [37].…”
Section: Simulations Of Oligonucleosomesmentioning
confidence: 99%
“…The linker histone (LH) protein, and its sub-variants, also play pivotal roles in the chromatin compaction 9, 10, 11, 12, 13, 14, 15 . The LH protein binds the nucleosome core at its dyad axis, close to both exiting and entering DNA strands.…”
Section: Introductionmentioning
confidence: 99%